Transactions/List Pricing - Seidmann, Daniel J. (Econometrica, 1990)
Supposethat a representative downstream firm must buy relationship-specific capital before an upstream monopolist is privately informed of its unit costs.We show that the upstream firm will write a contract before the downstream firm invests, specifying a maximum (list) price which may be discounted when costs are low.This model therefore rationalizes transactions/list pricing: a prevalent mode of inter-firm trading.We use our results to explain Stigler and Kindahl's findings on medium-term price dynamics.